The performance-based seismic response of special steel MRF: Effects of pulse-like ground motion and foundation safety factor. (December 2020) - Mashhadi, Sima; Asadi, Azita; Homaei, Farshad; Tajammolian, Hamed
Abstract: This study aims to investigate the effect of near-fault pulse-like earthquake ground motions as well as the foundation safety factor, on the performance-based seismic response (PBSR) of special steel moment-resisting frame (MRF). The Beam on the Nonlinear Winkler Foundation (BNWF) approach was employed for modeling the soil-foundation system. In this regard, values of 2, 3, and 5 were considered for the foundation vertical safety factor ( FSv ). The PBSR of the MRF has been assessed under 32 far-fault (FF) ground motions as well as 55 near-fault (NF) pulse-like records, through Incremental Dynamic Analyses (IDAs). The effects of extracted pulses and residual components of near-fault records were investigated as well. Results show that regardless of the earthquake record type, FSv has no considerable effect on the performance-based drift demand in the structure. However, larger settlement and rotation of the foundation are expected when a small FSv is accounted for. This leads to difficulties in providing the Immediate Occupancy ( IO ) performance objective for structures with operational performance levels. The effect of the input record type on the median foundation settlement is also inconsiderable. As well, a similarity was observed between the seismic performance of the structure under the residual components and the far-fault records. What's more, neither the extracted pulses nor the residual components of near-fault earthquake records can represent the original near-fault pulse-like records. Also, the residual component plays an important role in the structural responses under low-intensity earthquake events.